Urinary and intestinal health of nursing professionals in pandemic times of COVID-19: a theoretical reflection (Research, Society and Development, 2021)
Objective: To analyze the impact of the COVID-19 pandemic on the urinary and intestinal health of nursing professionals. Method: theoretical-reflective study with three thematic axes: i) nursing guidelines aimed at preventing urinary problems; ii) nursing guidelines aimed at preventing intestinal problems; iii) nursing work in pandemic time. Results: Unhealthy working conditions are observed in the health sector, characterized by undersized personnel and material shortages. Above all, with the COVID-19 pandemic, there was a shortage of Personal Protective Equipments. It is also asserted that vesting and intense work make it difficult for professionals to adopt practices that ensure urinary and intestinal health. It is important to adopt practices that enable urinary health: sitting position to urinate, appropriate time for complete bladder emptying, facility of toilet access during work, adequate fluid intake, reduction of bladder irritating substances such as caffeine and citrus. As well, there are guidelines to guarantee intestinal health: fiber diet; fluid intake; regular physical activity; use of a support to improve body posture at the time of evacuation, establish an evacuation routine. Conclusion: It is relevant to create means to socialize the knowledge about the promotion of urinary and intestinal health of professionals, as well as to stimulate managers to make possible means that guarantee this condition, improving the resizing of the teams and aiming at reducing complications such as constipation and urinary incontinence, among others.